(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article examines the process of commercialization of non-profit sports organizations and its impact on the development of sports. The authors discuss the reasons, problems and prospects for commercialization, and also propose key strategies for the successful implementation of this process.